2019
DOI: 10.26656/fr.2017.4(3).220
|View full text |Cite
|
Sign up to set email alerts
|

Olive (Olea europea) oil: physico-chemical characterization and antioxidant activities in vitro and in vivo

Abstract: Olive oil, especially extra virgin olive oil, gained popularity recently due to its beneficial effects toward human health. Olive oil contained high amounts of monounsaturated fatty acids, especially oleic acid (C18:1) and some minor components such as tyrosol and hydroxytyrosol which are important to human health. Olive oils have been reported to have antioxidant in vitro and in vivo. This article reviewed some physico-chemical properties and antioxidant activities of olive oil either in vitro or in vivo. Oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The findings follow the same trend of the difference between TPC and TFC (Table 1) . Literature data showed that FRAP method has limitation which is unable to measure polyphenolic compounds and thiols in which the total reducing power was significantly correlated with the phenolic compounds 73) and squalene (Table 5) . The results are in good agreement with the literature data where most of the compounds in OO are not phenolic compounds as a huge difference was observed between the TPC and TFC values, therefore, a great discrepancy was observed between OO and the other oil extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The findings follow the same trend of the difference between TPC and TFC (Table 1) . Literature data showed that FRAP method has limitation which is unable to measure polyphenolic compounds and thiols in which the total reducing power was significantly correlated with the phenolic compounds 73) and squalene (Table 5) . The results are in good agreement with the literature data where most of the compounds in OO are not phenolic compounds as a huge difference was observed between the TPC and TFC values, therefore, a great discrepancy was observed between OO and the other oil extracts.…”
Section: Resultsmentioning
confidence: 99%